Integrative taxonomic review of the genus Rhodostrophia Hübner, 1823 and its allied genus Tanaotrichia Warren, 1893 (Lepidoptera: Geometridae) from the Western Himalaya - Kumari, Shabnam; Bandyopadhyay, Uttaran; Uniyal, Virendra Prasad; Chandra, Kailash; Hausmann, Axel (Zootaxa, 2024)
The genus Rhodostrophia Hübner, 1823 and its close ally Tanaotrichia Warren, 1893 (Geometridae: Sterrhinae) are reviewed from the North Western and Trans Himalayan regions of the Indian Himalaya along with some specimens from the Pakistan. In total, eight species were studied—seven Rhodostrophia spp. and one species of Tanaotrichia—with detailed morphological and genital characteristics. Rhodostrophia borealis stat. n. is raised from subspecies of R. cinerascens to species level after studying external morphology and distinct genitalia-based diagnostic features. However, this warrants further validation following the barcode sequencing of R. cinerascens. Illustrations of habitus, including type specimens, are provided along with images of genitalia and the sequence data of the mitochondrial cytochrome c oxidase subunit I (COI 5′ terminus) gene. A checklist of Indian Rhodostrophia and Tanaotrichia species is included with information on their documented distributional range.